Genome-Wide Analysis of SRNF Genes in Gossypium hirsutum Reveals the Role of GhSRNF18 in Primary Root Growth - Yu, Li; Zhang, Shuojun; Liu, Hailun; Wang, Yufei; Wei, Yiting; Ren, Xujiao; Zhang, Qian; Rong, Junkang; Sun, Chendong (Frontiers in Plant Science, 2021)
Root systems are instrumental for water and nutrient uptake and for the anchorage of plants in the soil. Root regulating GL2-interacting repressors (GIRs) containing a Short RING-like Zinc-Finger (SRNF) domain, but there has been no comprehensive characterization about this gene family in any plant species. Here, we renamed the GIR-like proteins as SRNF proteins due to their conserved domain and identified 140 SRNF genes from 16 plant species including 24 GhSRNF genes in Gossypium hirsutum. Phylogenetic analysis of the SRNFs revealed both similarities and divergences between five subfamilies. Notably, synteny analysis revealed that polyploidization and whole-genome duplication contribute to the expansion of the GhSRNF gene family. Various cis-acting regulatory elements were shown to be pertinent to light, phytohormone, defense responsive, as well as meristem regulation. Furthermore, GhSRNF2/15 were predominantly expressed in root, whereas the expression of GhSRNF18 is positively correlated with the primary root (PR) length in Gossypium hirsutum, quantified by quantitative real-time PCR (qRT-PCR). Over-expression of GhSRNF18 in Arabidopsis and virus-induced gene silencing (VIGS) of GhSRNF18 in Gossypium hirsutum revealed the role of GhSRNF18 in primary root growth. The over-expression of GhSRNF18 in Arabidopsis resulted in an increase of meristematic activities and auxin accumulations in PRs, which were consistent with the transcriptomic data. Our results suggest that GhSRNF18 positively regulates the PR growth. This study increases our understanding of the SRNF gene family in plants and provides a novel rationale for the further investigation of cotton root morphogenesis regulated by the GhSRNFs.